Open educational resources: An analysis of the learning objectives referenced by Bloom’s digital taxonomy - Ortiz, José Oxlei de Souza; Kwecko, Viviani; Tolêdo, Fernando; Devincenzi, Sam; Botelho, Silvia Silva da Costa (Seven Editora, 2023)
This article presents an analysis of educational metadata related to the learning objectives employed in Educational Objects and in teachers’ activities at PhET Colorado. We have as main question, how the teachers have appropriated the educational objects available in PhET for the construction of activities. To this end, the research is based on the cognitive principles of Bloom’s digital taxonomy and its adaptations to classify learning objectives. As a result, we found that teachers apply learning objectives in a more diversified way in the construction of their activities, and explore the six levels of taxonomy in a more harmonious way. DOI:https://doi.org/10.56238/alookdevelopv1-196